Irradiação de morangos: limiares de rejeição e detecção sensorial e impacto da tecnologia de conservação sobre a aceitação e as percepções dos consumidores - Lima Filho, Tarcísio (2013)
Recently there have been numerous outbreaks of disease due to consumption of raw or minimally processed fruits and vegetables contaminated with pathogenic microorganisms. Strawberry is a fruit that has presented such contamination and, besides, it has a short shelf life due to fungal rot. Faced with such problems, experts in food preservation have suggested the use of irradiation, a non-thermal preservation method that eliminates insects, pests and pathogens and spoilage microorganisms and delays ripening, budding and aging of fruits and vegetables. Despite being accepted scientifically as a great conservation method and its use being permitted and regulated in many countries, the commercial use of irradiation has been limited by the rejection of consumers. Given this context, the aim of this study was to determine the radiation doses from which begin to occur rejection by the consumer and detection of sensory changes caused by irradiation of strawberry; to investigate the sensory acceptance of irradiated strawberries; the influence of non-sensory characteristics on consumer attitudes; the sensory, physicochemical and microbiological changes caused by irradiation of strawberry; the most important factors of irradiated strawberry packaging to the consumer and the ideal packaging for irradiated strawberry; and the thoughts, behavior and profile of consumers in relation to irradiated food. By preference paired testing in the method of constant stimuli, the dose of 3.6 kGy was determined as the consumer rejection threshold of irradiated strawberry; it was higher than the calculated detection threshold (0.405 kGy). By analyzing microbiological and physico-chemical characteristics it was found that the dose of 3.6 kGy is effective in reducing the microbial load of fungi, mesophilic and coliforms up to 15 days of storage. The results of physicochemical analyzes suggested that irradiation of strawberries do not cause great changes in total titratable acidity, pH, soluble solids and sugars. However, the results also suggested that the irradiated strawberry at 4 kGy may have a higher content of reducing sugars than non-irradiated or irradiated strawberries at lower doses; and that strawberry firmness decreased with the increase of irradiation dose. Paired comparison test for sweet taste showed that the use of higher doses of irradiation (4 kGy) caused greater intensity of perceived sweetness on strawberries. The three sessions of acceptance tests (blind test, test with treatment information given to strawberry and test with information of treatment given to strawberry and a text explaining the irradiation process), of the control strawberry (non-irradiated) and the irradiated strawberry at a dose of 3.6 kGy showed that there is significant difference between the samples in the blind test; treatment information generated negative influence on consumer acceptance and that consumer acceptance of irradiated strawberries at 3.6 kGy increased in the presence of a text with information about the irradiation process, and it did not differ from the acceptance of the control strawberry. The results obtained with the ratings-based conjoint analysis and choice-based conjoint analysis, in which 144 consumers participated, demonstrated that factors additional information and radura symbol (symbol of irradiated food) have great influence on the evaluation of consumers. The factor information of the preservation method showed no significant influence (p < 0.001) in consumer choice. However, for a part of the consumers (n = 8), the presence on the packaging of the information "food treated by ionization process" is primordial to a greater intent to purchase; and packaging containing such information was the one that obtained the highest choice probability. Thus, the ideal packaging for irradiated strawberry must include the information "food treated by ionization process", the additional information "to ensure freshness and quality for longer" and the presence of radura symbol (symbol of irradiated food). Brazilian law determines the presence of the term "irradiation" on the front of the packaging of irradiated products; however this study demonstrated that a part of the population has rejected this term, preferring the term "ionization". By applying a behavioral and sociodemographic questionnaire it was observed that the majority of consumers is neofobic, has little knowledge about the irradiation process, is concerned about the use of this method of preservation and has low purchase intent for irradiated foods. We also verified that consumers that have knowledge about the process of food irradiation tend to buy irradiated foods; and that young people, single, with higher levels of education and higher family income tend to have greater knowledge about the process of food irradiation, and that they are less concerned about the use of this technology and have higher purchase intention for irradiated food. As an overview of this study, it was possible to determine a dose of radiation that will serve as a guideline for producers and industries that market or intend to market irradiated strawberries. Moreover, it was possible to provide information about the thoughts and behaviors of consumers about irradiated food, and that these data will be useful in adopting strategies aimed at increasing the acceptance of irradiated food